2018
DOI: 10.3390/rs10020340
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Rice Phenology Based on Backscattering Characteristics of Multi-Temporal RADARSAT-2 Datasets

Abstract: Accurate estimation and monitoring of rice phenology is necessary for the management and yield prediction of rice. The radar backscattering coefficient, one of the most direct and accessible parameters has been proved to be capable of retrieving rice growth parameters. This paper aims to investigate the possibility of monitoring the rice phenology (i.e., transplanting, vegetative, reproductive, and maturity) using the backscattering coefficients or their simple combinations of multi-temporal RADARSAT-2 dataset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 43 publications
6
26
0
Order By: Relevance
“…Water in the agricultural field was also drained out causing a soil moisture reduction in August 2017. Moreover, we can see the maximal values of σ • VV and σ • VH appearing at the maturity stage after the maximum of greenness index are consistent with the study of He et al [90]. Previous studies showed that σ • VH correlated with the rice development stage [5,41,45].…”
Section: Data Analysis and Accuracy Assessmentsupporting
confidence: 92%
“…Water in the agricultural field was also drained out causing a soil moisture reduction in August 2017. Moreover, we can see the maximal values of σ • VV and σ • VH appearing at the maturity stage after the maximum of greenness index are consistent with the study of He et al [90]. Previous studies showed that σ • VH correlated with the rice development stage [5,41,45].…”
Section: Data Analysis and Accuracy Assessmentsupporting
confidence: 92%
“…Moreover, the amount of cross-pol components has increased during this period. A similar type of increase in cross-pol components from transplantation to maturity stages was reported by He et al (2018). The shift towards the Z2 and Z5 zones indicates an even-bounce scattering mechanism of the scattered EM wave.…”
Section: Temporal Variation Of θ Fp and θ Cp For Fp And Cp Datasupporting
confidence: 80%
“…Considering the X-band (8-12 GHz) radar, several types of research used the sensors: TerraSAR-X [31][32][33][34] and COnstellation of small Satellites for the Mediterranean basin Observation (COSMO)-SkyMed [33,[35][36][37][38]. Among the C-Band radar sensors (4-8 GHz) used to map the rice crops were: European Remote Sensing Satellite (ERS) [12,[39][40][41], Radarsat [42][43][44][45][46][47], and Advanced Synthetic Aperture Radar (ASAR) [48][49][50][51][52]. Finally, studies on rice mapping with L-band radar sensors (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) used the ALOS Phased Array type L-band Synthetic Aperture Radar (PALSAR) [53][54][55].…”
Section: Introductionmentioning
confidence: 99%